PENERAPAN PENDIDIKAN KARAKTER MELALUI STRATEGI PEMBELAJARAN PAI DI SMK IHYAUL DUKUN GRESIK - Safiqo, Tatik (ILJ: Islamic Learning Journal, 2023)
This study aims to determine the application of character education through teaching strategies for Islamic religious education teachers, Supporting and Inhibiting Factors for the Implementation of Character Education Through Teaching Strategies for Islamic Religious Education Teachers at SMK Ihyaul Ulum Dukun Gresik. The two questions above were answered through a literature review. Various literature related to the research problem was collected and then selected and then presented along with the analysis. This type of research is a non-statistical qualitative research. Informant subjects in this study consisted of school principals and teachers. This study uses data collection techniques in the form of observation, interviews, and documentation. To analyze the research data used qualitative descriptive techniques. The results of the research show: Implementation of character education must be in line with educational orientation. The pattern of learning is carried out by instilling certain moral values ??in children that are beneficial for their personal development as individual as well as social beings. Character education carried out at Ihyaul Ulum Vocational High School had actually been implemented before the character education discourse proclaimed by this nation emerged, since the establishment of Ihyaul Ulum Vocational School as a school that "breathes" Islam, of course in practice the learning has already implemented an ahklaq (character) education program in accordance with Islamic guidance itself. The supporting factors in the formation of students' religious character include: Habits or traditions that exist in Ihyaul Ulum Vocational School, namely habits in daily life, Student awareness is the most important and main thing of the supporting factors is student self-awareness that grows from students to always carry out actions commendable in his life, motivation and support from both parents, and also the community around the school who also support the learning process.